Design of INS/GNSS Precise Posture Measurement and Positioning System for Complex System. Issue 1 (1st November 2022) - Han, Rong; Yang, Jianfen; Tang, Yumin; Yang, Liben
Abstract: In this paper, aiming at the robustness of the UAV control system and the accuracy of positioning and mapping in complex situations, the visual odometry is used as the front end of the positioning and mapping system, and the data of the IMU inertial sensor is fused on the basis of the monocular camera. The analysis completes the loosely coupled initialization process; the back-end constructs the cost function to realize the tightly coupled optimization, and uses the loop closure detection relocation and the four degree of freedom graph optimization to realize the nonlinear optimization. It is verified by simulation that the algorithm can improve the visual robustness in time when the UAV moves quickly or the scene has wrong results, so that the trajectory captured by the camera and the real-time construction map maintain global consistency, effectively eliminating the integral drift of the IMU, and correcting The noise of the IMU improves its positioning accuracy.